Course of Type 2 Diabetes Mellitus with Covid-19 - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
Diabetes mellitus is one of the major health problems of the 21st century. Around the world, about 382 million people suffer from diabetes, and this figure is only growing every year, which leads to early disability of the population. Purpose of the study: To identify the features of the course of diabetes mellitus against the background of coronavirus infection based on literature data. Materials and methods: A comparative analysis and synthesis of information on the course of type 2 diabetes mellitus in COVID-19 was carried out on the basis of literature data: a review of articles, highlighting key scientific studies and reviews. The selection of literature was carried out in the databases: eLIBRARY, CyberLeninka, PubMed. Results and discussion: The severe course and high incidence of deaths in patients with diabetes is explained by the peculiarities of the interaction of the virus and its receptor under conditions of hyperglycemia. The cytotoxic effect of the virus on pancreatic islet cells leads to the development of insulin deficiency. Conclusion: Mortality from COVID-19 in patients with type 2 diabetes mellitus is more than twice as high. There is a decrease in O2 saturation with an increase in blood glucose levels. A number of studies have shown that glycemic levels ranging from 3.9 to 10.0 mmol/l are associated with significantly lower mortality than those with glycemic levels exceeding 10 mmol/l. During the X-ray examination of patients with diabetes, bilateral pneumonia predominated.